3D hydrodynamical modeling of circularization in binary systems - Sirotkin, F. V. (Одеські астрономічні публікації, 2017)
Results of Three-dimensional hydrodynamical modelling of circularization process in binary systems at early stages of evolution are presented. It is shown, that circularization for systems in which the components fill their Roche lobe and are on the Hayashi track, occurs for times about hundreds of orbital periods. Thus, the binary systems such as V382 Cyg reach on the Main Sequence, having already a circular orbit.